Twelve tips for clinical teaching with telemedicine visits. (2nd January 2022) - Hovaguimian, Alexandra; Joshi, Ashwini; Onorato, Sarah; Schwartz, Andrea Wershof; Frankl, Susan
Abstract: Telemedicine is now an established mode of clinical care for most medical specialties, and clinical teachers must teach and precept learners in this modality. However, faculty need training on how best to teach students when caring for patients via telemedicine. Effectively incorporating learners into telemedicine visits to optimize their education is a critical skill for clinical teachers. In this article, we review 12 practical tips unique to telemedicine to engage and educate undergraduate medical education learners in building their clinical skills. We outline synchronous and asynchronous elements before, during, and after the patient encounter to facilitate teaching while improving patient care. These principles can also be adapted for teaching in other health professions as well as postgraduate medical education.